Mitogen-activated protein kinase and neural specification in Xenopus - Uzgare, Aarti R. (The National Academy of Sciences, 1998)
We have investigated the activity and function of mitogen-activated protein kinase (MAPK) during neural specification in Xenopus. Ectodermal MAPK activity increased between late blastula and midgastrula stages. At midgastrula, MAPK activity in both newly induced neural ectoderm and ectoderm overexpressing the anterior neural inducer noggin was 5-fold higher than in uninduced ectoderm. Overexpression of MAPK phosphatase-1 (MKP-1) in ectoderm inhibited MAPK activity and prevented neurectoderm-specific gene expression when the ectoderm was recombined with dorsal mesoderm or treated with fibroblast growth factor (FGF). Neurectoderm-specific gene expression was observed, however, in ectoderm overexpressing both noggin and MKP-1. To evaluate the role of MAPK in posterior regionalization, ectodermal isolates were treated with increasing concentrations of FGF and assayed for MAPK activity and neurectoderm-specific gene expression. Although induction of posterior neural ectoderm by FGF was accompanied by an elevation of MAPK activity, relative MAPK activity associated with posterior neural fate was no higher than that of ectoderm specified to adopt an anterior neural fate. Thus, increasingly posterior neural fates are not correlated with quantitative increases in MAPK activity. Because MAPK has been shown to down-regulate Smad1, MAPK may disrupt bone morphogenetic protein 4 (BMP-4) signaling during neural specification. Our results suggest that MAPK plays an essential role in the establishment of neural fate in vivo.